Continuing Professional Development in Social Work - Halton, Carmel; Scanlon, Margaret, 1965-; Powell, Fred W. (Book collections on Project MUSE., 2014)
Continuing professional development (CPD) has become a defining issue in 21st century social work. There is widespread consensus in favour of CPD. But what is it? Are there discernible international trends? What are the barriers to participating in CPD? What do social workers think about and want from CPD? This book seeks to answer these questions. Based on a survey and interviews with social work practitioners, it offers a unique insight into the possibilities and challenges of CPD and the issues it presents for newly qualified and experienced social workers in practice.